Lamellar orientation evolution of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) thin film with 3-hydroxyhexanoate comonomer content difference. Issue 1 (2nd January 2021) - Chen, Yujing; Yang, Chunming; Kong, Zhenxing; Ou, Juhua; Yang, Rui; Dai, Zilin; Noda, Isao; Jung, Young Mee
Abstract: The influence of 3-hydroxyhexanoate (HHx) comonomer molar fraction on the morphology and lamellar packing of poly(3-hydroxybutyrate- co -3-hydroxyhexanoate) (PHBHx) thin film under spatial confinement were carefully investigated by scanning probe microscope (SPM) and synchrotron radiation grazing-incidence wide-angle X-ray scattering (GIWAXS) measurements. It was found that the HHx comonomer content plays an important role on the crystalline structure of PHBHx thin film on Si substrate. The morphology evolution of PHBHx thin film with increasing HHx content was evident. The crystalline lamellae are packed more loosely with the increase of HHx molar fraction, while the lamellar thickness is decreased.